Household participation in a Payments for Environmental Services programme: the Nhambita Forest Carbon Project (Mozambique) - Hedge, R.; Bull, G.Q.; Wunder, Sven; Kozak, R. (Cambridge University Press, 2015)
Quantitative research on household participation in the Payments for Environmental Services (PES) programme remains scarce. This paper aims to determine the key factors influencing household participation in a PES programme in Mozambique. Questionnaire-based quarterly surveys were conducted with 290 randomly selected households. We used the instrumental variables technique to identify the factors influencing household participation. The instrumental variables used for forest dependence were: household head born in the village, duration of residence of the household head in the village, ethnicity of the household head, business ownership of the household head and off-farm income of the household. The results show that education of household head and households' trust towards community members positively influenced household participation in PES, while forest dependence influenced it negatively. Future PES projects may thus need to focus more on developing social capital and the resource dependence of households.